2021
DOI: 10.1021/acs.est.0c07408
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Histidine Reactivity and Byproduct Formation during Peptide Chlorination

Abstract: The covalent modifications resulting from chlorine reactions with peptide-bound amino acids contribute to pathogen inactivation and disinfection byproduct (DBP) formation. Previous research suggested that histidine is the third most reactive of the seven chlorine-reactive amino acids, leading to the formation of 2chlorohistidine, 2-oxohistidine, or low-molecular-weight byproducts such as trihalomethanes. This study demonstrates that histidine is less reactive toward formation of chlorine transformation product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Recent studies investigating the chlorination of amino acids indicated that the yields of DBPs such as THMs and HANs were typically low (<5%), while other unidentified transformation products accounted for a greater proportion of TOX. 50 Moreover, the yield of TOCl decreased significantly from 218.5 to 81.4 μg-Cl/mg-C along the Yangtze River. From the perspective of chlorine reaction chemistry, the decreasing trend of the TOCl yield implied that electron transfer rather than halogen substitution played a more important role in chlorination.…”
Section: ■ Materials and Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…Recent studies investigating the chlorination of amino acids indicated that the yields of DBPs such as THMs and HANs were typically low (<5%), while other unidentified transformation products accounted for a greater proportion of TOX. 50 Moreover, the yield of TOCl decreased significantly from 218.5 to 81.4 μg-Cl/mg-C along the Yangtze River. From the perspective of chlorine reaction chemistry, the decreasing trend of the TOCl yield implied that electron transfer rather than halogen substitution played a more important role in chlorination.…”
Section: ■ Materials and Methodsmentioning
confidence: 78%
“…Therefore, the yields of commonly known DBPs are typically low during chlorination of proteins, accompanying a high proportion of UTOX. Recent studies investigating the chlorination of amino acids indicated that the yields of DBPs such as THMs and HANs were typically low (<5%), while other unidentified transformation products accounted for a greater proportion of TOX . Moreover, the yield of TOCl decreased significantly from 218.5 to 81.4 μg-Cl/mg-C along the Yangtze River.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Likewise, imidazole-derivatives (e.g. L-histidine, carnosine, carcinine) and thio-imidazolederivatives (ergothioneine and sea urchin-derived ovothiol) have been identified as potent chlorination stress inhibitors (111)(112)(113).…”
Section: Endogenous Phytochemical and Synthetic Hocl-antagonists: Ant...mentioning
confidence: 99%